Desa Pesantren Dan reProDuksi kiai kamPung - Syamsul, Hadi; Soetarto, Endriatmo; Sunito, Satyawan; Pandjaitan, Nurmala K. (Analisis: Jurnal Studi Keislaman, 2016)
Pesantren serves as an educational institution (Islamic) as well as social institutions are generally based in the rural. Even the pattern in rural Javanese life was also much influenced by the culture and values of the pesantren. Not only student from the local village, but the students from various regions are also many who come to study in the pesantren. After graduating from the pesantren they go home, and among them there is a role in their communities. They learn Islamic knowledge covering: the Qur’an and Tafseer, Hadith, theology, ethics, Islamic jurisprudence, gramer and morphology (nahwu- shorof). In a rural environment, he is moving the activities of  religious  education,  mental-spiritual  and  socio-civic. When pesantren has developed with its own correlated to the progress of the village. The village of pesantren are a model of rural development that progress is largely supported by his values and traditions of Islam. Santri of pesantren graduates who have returned to the village and have a strong will devote themselves to the interests of society become essential factor for the preservation of social development in the rural. So, in this context the strategic value of the role of the village kiai in community development in rural areas.